Early Detection of Non-Communicable Diseases at the Integrated Guidance Post in the Work Area of the Way Jepara Community Health Center, East Lampung Regency - Elmida Siska; Suci Hadia Yunda; Riza Tsalatsatul Mufida; Miftakhur Rohmah (Universitas STRADA Indonesia, 2024)
Non-communicable diseases (NCDs) have been the leading cause of death in the world since the third millennium. According to WHO in 2000, the proportion of deaths due to NCDs in the world continued to increase from 47% in 1990 to 56%. This Community Service was carried out with a one-group pretest posttest, namely by measuring the level of knowledge before and after treatment. This treatment was to provide counseling on knowledge of early detection of non-communicable diseases at the Integrated Development Post. The results of this community service showed an increase in counseling from before counseling in the category of poor knowledge by 9, increasing after counseling in the good category by 12. Knowledge increased from before and after counseling. This was influenced by counseling on Early Detection of Non-Communicable Diseases at the Integrated Development Post, so that the Community would become aware of the material.